2018
DOI: 10.3390/s18051562
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis as a Tool to Identify Concentrations from Strongly Overlapping Gas Spectra

Abstract: We applied a multivariate analysis (MVA) to spectroscopic data of gas mixtures in the mid-IR in order to calculate the concentrations of the single components which exhibit strongly overlapping absorption spectra. This is a common challenge in broadband spectroscopy. Photoacoustic (PA) measurements of different volatile organic compounds (VOCs) in the wavelength region of 3250 nm to 3550 nm served as the exemplary detection technique. Partial least squares regression (PLS) was used to calculate concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In order to obtain the concentrations of individual substances of a measured spectrum containing multiple substances, multivariate analysis (MVA) [21,22] can be applied. This was also demonstrated in a recent work, where PA measurements of volatile organic compounds from strongly overlapping spectra in the mid IR region were evaluated [23]. Well-known multivariate regression models are the multiple linear regression, the principal component regression, and the partial least-square regression (PLSR), whereby the latter has become the standard method for spectroscopy [21,24].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…In order to obtain the concentrations of individual substances of a measured spectrum containing multiple substances, multivariate analysis (MVA) [21,22] can be applied. This was also demonstrated in a recent work, where PA measurements of volatile organic compounds from strongly overlapping spectra in the mid IR region were evaluated [23]. Well-known multivariate regression models are the multiple linear regression, the principal component regression, and the partial least-square regression (PLSR), whereby the latter has become the standard method for spectroscopy [21,24].…”
Section: Introductionmentioning
confidence: 87%
“…As output values, loading and score matrix of X and Y, explained variance (in %) by the model by each LV, and the PLSR coefficients are computed. The PLSR coefficients are required to calculate target values (concentrations) out of initial data (spectra): where is the PLSR coefficient matrix, is the predictor matrix (spectra), the response matrix (concentrations), and the error matrix [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the spectral features of the single substances are broad and overlap strongly, the spectra evaluation requires a multivariate analysis. The general suitability of Partial Least Squares Regression (PLSR) to determine the absolute concentrations of different components of a mixture has been demonstrated [2,3]. However, the according study also revealed certain limitations of this evaluation method.…”
Section: Introductionmentioning
confidence: 99%